Dual-bed catalytic system for direct conversion of methane to liquid hydrocarbons: study of selected reaction parameters - Saidina Amin, Nor Aishah; Ammasi, Sriraj (2005)

(untitled)
A dual-bed catalytic system has been investigated for the direct conversion of methane to liquid hydrocarbons. In this system, methane is converted in the first stage to OCM products over La/MgO catalyst whilst the OCM products are oligomerized to liquid hydrocarbons over Ni loaded HZSM-5 zeolite catalyst. The influence of reaction temperature (650-800Â°C), amount of nickel loading (0-3 wt%) and CH4/O2 ratio (4-10) on the process has been studied under atmospheric conditions. The results implied that the Bronsted acid sites of HZSM-5 which acts as an agent for oligomerization would easily be victimized at higher reaction temperature and thus, limits the oligomerization reaction. Oxygen is absolutely necessary for the activation of methane, but it must be kept at favored value in order to suppress the undesirable oxidation reactions. Experimental results also reveal that the unnecessary effect can be minimized by optimizing the amount of nickel loaded on the HZSM-5 catalyst when applied as second bed. This exploration suggests that the concept of dual-bed system is an attractive candidate for methane utilization to produce liquid hydrocarbons.